Quantifying the Variability of Solar Energy Fluctuations at High–Frequencies through Short-Scale Measurements in the East–Channel of Mozambique Conditions (American Journal of Energy and Natural Resources, 2024)
The solar power output of a solar plant is directly affected by changes in solar energy. To enhance the accuracy, durability, and efficiency of solar projections, it was necessary to quantify the rapid fluctuations in solar energy on a short–scale in the conditions of eastern Mozambique. An analytical approach was utilized to measure the high–frequency variations in the clear–sky index (K*t) and its increments (∆K*t). The results indicate that the K*t fluctuations in the nine stations along the eastern–channel of Mozambique ranged from 0.0001 to 0.9999, with a probability density (PDF) of fluctuations limited to 0.9991. Through statistical analysis, it was determined that ∆K*t reaches its maximum value near zero. Days with intermediate–sky conditions exhibited high PDF values of approximately 1.0 and greater deviation, while clear and cloudy–sky days displayed consistent solar energy frequencies and a lower tendency for K*t deviation. In conclusion, the correlation between high–fluctuation variability diminishes rapidly for shorter intervals. Furthermore, high–frequencies of fluctuations are observed during the hot and rainy season, whereas low frequencies are observed during the cold and dry season.